ADJECTIVES IN THE EXPRESSION OF EPISTEMIC MODALITY IN APPLIED LINGUISTICS RESEARCH ARTICLES - Attapol Khamkhien (Universitas Islam Sumatera Utara (UISU), 2021)
Research in academic writing has shown that writers have a strong tendency to communicate their ideas interactively with readers. This study examines how professional writers use adjectives as part of interactional metadiscourse when writing research articles. A total of 255 research articles published in distinguished journals in the field of applied linguistics between 2015 and 2020 were systematically compiled and quantitatively and qualitatively analysed. The extent to which epistemic adjectives and typical phraseological patterns are used in research articles was investigated with the help of corpus linguistics methods, as was their epistemic strength indicated by writers. The interpersonal model of metadiscourse was used as the theoretical framework for the study. The findings suggest that the academic writing corpus, in essence, is interactionally oriented, while the use of adjectives as an epistemic modality reflects a methodical approach by article writers when presenting propositions and discussing their knowledge claims. This study provides a deeper understanding of these linguistic features to impact the reader. Pedagogically, the study can be useful for teaching academic writing to postgraduate students and help them and novice writers develop writing competency through epistemic devices, especially in research articles intended for publication.